PEMANFAATAN REGULASI PENDIDIKAN DASAR SEBAGAI LANDASAN PROFESIONALISME GURU SD - Nala Zulfia; Wina Maisafni Dunita; Desyandri; Zelhendri Zen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the utilization of basic education regulations as a primary foundation for enhancing teacher professionalism in elementary schools. Teachers hold a strategic role as change agents who determine the success of the learning process and the quality of human resources nationally. However, challenges such as limited 21st-century skills and differing perceptions of policies often hinder the optimization of teacher performance. The method used is a literature review, analyzing secondary data from reputable scientific articles. Analysis results show that education regulations provide a strong legal basis for governing teacher qualifications, certification, and competence. Strengthening professionalism can be achieved by synchronizing regulations with structured academic supervision programs and continuous development within learning communities. The study concludes that the effectiveness of regulations depends heavily on consistent supervision and adequate resource support. Proper policy implementation is proven to contribute significantly to improving the standards of pedagogical, personal, social, and professional competencies of elementary school teachers.